After Hegel : German Philosophy, 1840-1900 - Beiser, Frederick C., 1949- (Book collections on Project MUSE., 2014)
Histories of German philosophy in the nineteenth century typically focus on its first half-when Hegel, idealism, and Romanticism dominated. By contrast, the remainder of the century, after Hegel's death, has been relatively neglected because it has been seen as a period of stagnation and decline. But Frederick Beiser argues that the second half of the century was in fact one of the most revolutionary periods in modern philosophy because the nature of philosophy itself was up for grabs and the very absence of certainty led to creativity and the start of a new era.